Financial Behaviour and Determination of Foreign Exchange Risk Management Practices, Products and Techniques, and Their Use by Japanese Firms - Kawashima, Chisato (2007)
Exchange rate fluctuations are a major cause of uncertainty for companies which trade across countries and currencies in the severely competitive global market. There are many choices of financial techniques used to manage foreign exchange risk. This research has investigated foreign exchange risk management practices in four Japanese firms through semi-structured interviews. The most popular external financial method was forwards contracts. In internal financial techniques, policies where home currency based transactions were sought, were preferred as they allowed the firms to avoid foreign exchange exposures. Through the interviews the opinions of financial managers were investigated and their thoughts on the advantages and disadvantages of different foreign exchange risk management practises were revealed. Overall, it was found that all the interviewed firms were satisfied with the foreign exchange risk management practises implemented although some indicated that they were concerned with the sustainability of the practises currently used.